2018
DOI: 10.1111/and.13068
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of tadalafil and verapamil on testicular function and oxidative stress after torsion/detorsion in adult male rat

Abstract: Tadalafil and verapamil can be protected the testis tissue damage and replaced the testicular function by suppressing oxidative stress after testicular torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 24 publications
(41 reference statements)
15
56
0
Order By: Relevance
“…Also, a lot of drugs in this group, like amlodipine, nifedipine, verapamil and lidocaine, have antioxidant properties (Arena et al, 2017). Sarica et al (1999) reduce the I/R damage and the sperm parameters assessment in various groups indicated that verapamil cannot remarkably meliorate the sperm characteristics; it is perhaps based on verapamil calcium channel-blocking activity that perhaps blocked the Ca2+/Na+ channels of spermatozoa and could not increase the motility and percentage of normal spermatozoa (Ameli et al, 2018). Also, Juneja et al (1990) and Moger (1983) have revealed that sperm quality diminishes followed by administration of calcium channel blockers like verapamil (Juneja et al, 1990;Moger, 1983).…”
Section: Deepa Et Al In Research On the Impacts Of Heparin On Cell Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a lot of drugs in this group, like amlodipine, nifedipine, verapamil and lidocaine, have antioxidant properties (Arena et al, 2017). Sarica et al (1999) reduce the I/R damage and the sperm parameters assessment in various groups indicated that verapamil cannot remarkably meliorate the sperm characteristics; it is perhaps based on verapamil calcium channel-blocking activity that perhaps blocked the Ca2+/Na+ channels of spermatozoa and could not increase the motility and percentage of normal spermatozoa (Ameli et al, 2018). Also, Juneja et al (1990) and Moger (1983) have revealed that sperm quality diminishes followed by administration of calcium channel blockers like verapamil (Juneja et al, 1990;Moger, 1983).…”
Section: Deepa Et Al In Research On the Impacts Of Heparin On Cell Pmentioning
confidence: 99%
“…In a research about verapamil's protective effects on testicular tissue conducted byAmeli et al (2018), it was found that verapamil can *p < .05 compared with the sham group. In a research about verapamil's protective effects on testicular tissue conducted byAmeli et al (2018), it was found that verapamil can *p < .05 compared with the sham group.…”
mentioning
confidence: 99%
“…Testicular torsion is a urological emergency, which can ultimately cause losing of gonads (Ameli et al, 2018). Probability of this complication occurrence is high in pubertal period, but it can occur at any age (Gökçe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that I/R injury is relevant to high levels of MDA (Ameli et al, 2018;Avlan et al, 2005;Gökçe et al, 2010;Wilhelm Filho et al, 2004). Several studies have proved that I/R injury is relevant to high levels of MDA (Ameli et al, 2018;Avlan et al, 2005;Gökçe et al, 2010;Wilhelm Filho et al, 2004).…”
Section: Stevia Rebaudiana Is a Shrub With Numerous Medical Featuresmentioning
confidence: 99%
See 1 more Smart Citation